EULAR recommendations for the management of primary small and medium vessel vasculitis. Issue 3 (15th April 2008) - Mukhtyar, C; Guillevin, L; Cid, M C; Dasgupta, B; de Groot, K; Gross, W; Hauser, T; Hellmich, B; Jayne, D; Kallenberg, C G M; Merkel, P A; Raspe, H; et al.
Abstract : Objectives: To develop European League Against Rheumatism (EULAR) recommendations for the management of small and medium vessel vasculitis. Methods: An expert group (consisting of 10 rheumatologists, 3 nephrologists, 2 immunologists, 2 internists representing 8 European countries and the USA, a clinical epidemiologist and a representative from a drug regulatory agency) identified 10 topics for a systematic literature search using a modified Delphi technique. In accordance with standardised EULAR operating procedures, recommendations were derived for the management of small and medium vessel vasculitis. In the absence of evidence, recommendations were formulated on the basis of a consensus opinion. Results: In all, 15 recommendations were made for the management of small and medium vessel vasculitis. The strength of recommendations was restricted by low quality of evidence and by EULAR standardised operating procedures. Conclusions: On the basis of evidence and expert consensus, recommendations have been made for the evaluation, investigation, treatment and monitoring of patients with small and medium vessel vasculitis for use in everyday clinical practice.